2007
DOI: 10.1111/j.1472-765x.2007.02198.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Actinobacteria cultivated from environmental samples reveals bias in universal primers

Abstract: Aims:  The aims of this study were to develop media to cultivate actinomycetes, screen the resulting isolates with Actinobacteria‐specific primers, and examine the efficacy of detection of the actinobacterial isolates with universal primers. Methods and Results:  Soil‐extract medium was developed for a terrestrial bluff environment. Recovered isolates were subjected to polymerase chain reaction (PCR) with taxon‐specific primers to identify Actinobacteria. Universal bacterial primers 24f and 1492r (modified and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 38 publications
2
59
1
Order By: Relevance
“…This strategy made it challenging to identify two specific, opposing primers that would generate a readily detectable PCR product, and we therefore paired a target-specific forward primer with the same general reverse primer used in the original cloning exercise. (4,10,12) have shown that so-called "universal" primer sets are incapable of efficiently amplifying all targets, even those from pure cultures and with perfect sequence matches, casting doubts on the universality of such primers. Further, other groups have suggested that 16S rRNA gene group-specific primers can produce upwards of 25% nontarget amplification, making them unsuitable for qPCR (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy made it challenging to identify two specific, opposing primers that would generate a readily detectable PCR product, and we therefore paired a target-specific forward primer with the same general reverse primer used in the original cloning exercise. (4,10,12) have shown that so-called "universal" primer sets are incapable of efficiently amplifying all targets, even those from pure cultures and with perfect sequence matches, casting doubts on the universality of such primers. Further, other groups have suggested that 16S rRNA gene group-specific primers can produce upwards of 25% nontarget amplification, making them unsuitable for qPCR (10).…”
Section: Discussionmentioning
confidence: 99%
“…(4,10,12) have shown that so-called "universal" primer sets are incapable of efficiently amplifying all targets, even those from pure cultures and with perfect sequence matches, casting doubts on the universality of such primers. Further, other groups have suggested that 16S rRNA gene group-specific primers can produce upwards of 25% nontarget amplification, making them unsuitable for qPCR (10). It has also been suggested that reliance on the slowly evolving 16S rRNA gene makes it difficult to recognize recent events in the evolutionary history of a species, such as those associated with incipient speciation (24), which might also be a contributing factor to the high levels of nonspecific binding for some of the primer sets employed here.…”
Section: Discussionmentioning
confidence: 99%
“…The cyclic conditions were as follows: initial denaturation at 94°C for 3 min, 35 cycles of 94°C for 1 min, 54°C for 1 min, and 72°C for 2 min, and final extension of 10 min at 10 min and hold at 4°C. The PCR products were confirmed by 1 % agarose gel electrophoresis (Farris et al 2007). …”
Section: Preparation and Analysis Of 16s Rrnamentioning
confidence: 99%
“…Polyspecific primers are usually designed to amplify multiple templates present in samples, often including a variety of organisms (Farris and Olsen, 2007). It is critical to design polyspecific primers that are specific enough to target only the taxonomic groups of interest but at the same time not biasing the PCR reaction toward only certain components of a population (Anderson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%